Analysis of methanol, fusel alcohols, and other volatile compounds of local specialty alcoholic beverages (wine, beer, and soju) in Korea - Dayoung Jeong; Young-Suk Kim (Applied Biological Chemistry)
Abstract The most commonly consumed local specialty alcoholic beverages in South Korea are wine, beer, and soju. These alcoholic beverages contain a wide variety of volatile components, including methanol and fusel alcohols, due to their different raw materials, manufacturing methods, and fermentative microorganisms. GC–MS combined with solid phase micro-extraction (SPME) was utilized to establish a simultaneous analytical method for methanol, fusel alcohols, and other volatile compounds in alcoholic beverages, which included 9 wine, 10 beer, and 10 soju samples. A total of 221 volatile compounds were identified, consisting of 6 acetals, 14 acids, 33 alcohols, 9 aldehydes, 2 amides, 13 benzene derivatives, 5 phenols, 81 esters, 8 furans, 16 ketones, 6 sulfides, 26 terpenes, 1 pyrazine, and 1 miscellaneous. Among the three types of alcoholic beverages, wine had the highest methanol content. In case of fusel alcohols, wine, beer, and soju contained 25, 16, and 14 alcohol components, respectively. In general, those main volatile components of wine, beer, and soju were esters, alcohols, and benzene derivatives. In beer, terpenes were detected at similar levels with alcohols. Volatile compounds contributing to the distinction between soju and beer were some alcohols, such as propan-1-ol, 2-methylpropan-1-ol, and 3-methylbutan-1-ol, and acids, such as octanoic acid, whereas wine samples were distinguished from other types of alcoholic beverages by some esters, such as methyl acetate, ethyl (E)-but-2-enoate, ethyl 3-hydroxybutanoate, and diethyl butanedioate, and some alcohols, such as hexan-1-ol, nonan-2-ol, and nonan-1-ol.